The role of probiotic strains of lactic acid bacteria in functional food - Polonchuk , Liudmyla (Problems of Environmental Biotechnology, 2021)
The necessity of daily consumption of high-quality functional sour-milk drink, namely kefir, is noted. Experiments have proven the high biological activity and value of this drink to prevent intestinal dysbacteriosis and improve digestive processes with regular use of this product.